(untitled) (Revista cientifica In Vestigium Ire, 2019)
In the Department of Boyacá, in the province of Ricaurte the cultivation of coffee is one of the products that has had great impact in recent times, given the quality of the grain that is produced, this due to climate, lands and geographical conditions of the region that favor it. During the year 2017, in the department of Boyacá, 8,065,974 kilos of coffee were harvested, in around 37 municipalities, Moniquirá, the capital of the province of Ricaurte, being the largest producer with 1,091,973 kilos (Carolina LealAcosta, 2018). Given the high coffee production that the municipality represents far the department, there is evidence of the need to guarantee the effective and agile sale of the product at regional, national and international levels. However, it lacks an information and knowledge system that facilitates the commercialization processes to attack the existing sales gaps from the producer to the final consumer. Therefore, this article seeks a solution alternative to the analysis of the coffee production chain from the commercialization link, since the coffee production chain exposed by the National Planning Department (NPD) does not contemplate the commercialization link, being this necessary to complete the production process. This is why the aim is to characterize and analyze the production chain, in arder to propase an information management model and also a technological strategic plan, which jointly allow generating greater competitiveness and added value to the marketing link of coffee in the municipality of Moniquirá.